Peroxiredoxin 6 regulates the phosphoinositide 3-kinase/AKT pathway to maintain human sperm viability. (24th October 2019) - Fernandez, Maria C; Yu, Alex; Moawad, Adel R; O'Flaherty, Cristian
Abstract: Peroxiredoxins (PRDXs) are antioxidant enzymes proven to control the levels of reactive oxygen species (ROS) and to avoid oxidative damage in the spermatozoon. Previously, we have shown that low amounts of PRDXs are associated with male infertility and that PRDX6 is the primary antioxidant defense in human spermatozoa, maintaining survival and DNA integrity (Gong et al., 2012, Fernandez and O'Flaherty, 2018 ). Oxidative stress can trigger different pathway cascades in the spermatozoa, including truncated apoptosis. It has been reported that the phosphorylation status of phosphoinositide 3-kinase (PI3K) and its target AKT (protein kinase B) prevent the spermatozoon from entering the truncated apoptotic cascade. Here, we aim to study the regulation of the PI3K/AKT pathway by PRDX6 and assess its role in maintaining sperm viability. Human semen samples were obtained over 1 year from 20 healthy non-smoking volunteers aged 22–30 years. Sperm viability, lipid peroxidation and apoptosis-like changes were determined by flow cytometry while phosphorylation of PI3K and AKT substrates were assessed by immunoblotting using anti-phospho-PI3K and anti-phospho-AKT substrates antibodies. We found that the addition of arachidonic acid and lysophosphatidic acid, products of PRDX6 calcium-independent phospholipase A2 (Ca 2+ -iPLA2 ), prevented loss of sperm viability and maintained the phosphorylation of PI3K. Antioxidant compounds such as D-penicillamine partially prevented the oxidative damage on spermatozoa that led to a reduction of their viability. Thus, other pathways can also participate in sperm survival and be regulated by PRDXs. In conclusion, PRDX6 contributes to the regulation of ROS production and the PI3K/AKT pathway for the maintenance of sperm survival.